Advanced signal integrity for high-speed digital designs - Hall, Stephen H. (John Wiley & Sons, 2009)
This book is designed to provide contemporary readers with an understanding of the emerging high-speed signal integrity issues that are creating roadblocks in digital design. Written by the foremost experts on the subject, it leverages concepts and techniques from non-related fields such as applied physics and microwave engineering and applies them to high-speed digital design—creating the optimal combination between theory and practical applications.